Nematoides entomopatogênicos visando o controle de Elasmopalpus lignosellus na cultura do milho - Magnabosco, Maria Eduarda Berlatto (2018)
The cornstalk borer, Elasmopalpus lignosellus (Zeller) (Lepidoptera: Pyralidae), is one of the pests responsible for the decrease of the productive potential of the corn, because it forms gallery on the stem, causing the tillering or death of the plant. Despite being considered a difficult-to-manage pest, it is currently used chemical control, via seed treatment and insecticide applications. However, the use of this method has presented low efficiency, besides generating problems due to incorrect use, insect resistance, population outbreaks, rise of secondary pests, increased production costs and increased human and environmental contamination. Initially, the virulence of the isolates, Heterorhabditis amazonensis MC01, H. amazonensis JPM3, H. amazonensis GL, Steinernema carpocapsae All and Heterorhabditis sp. Nepet 11 was tested on E. lignosellus pupae and caterpillars in the laboratory. The avarages were compared by the Scott-Knott test (p ≤ 0.05). Subsequently, the concentrations of 50, 100, 150 and 200 JI insect-1 of H. amazonensis GL for pupae and of H. amazonensis MC01 for caterpillars were tested in a completely randomized design with five replicates. Data were submitted to regression analysis. In greenhouse the concentrations of the isolates were again tested in vase containing corn. For caterpillars the concentrations of 190, 210, 230 and 250 JI larve-1 of H. amazonensis MC01 were tested following the completely randomized design with five replicates. For the pupae the concentrations 3380, 3500, 3620, 3740 JI vase-1 of H. amazonensis GL were tested following the same design with four replicates. Finally, the compatibility of phytosanitary products used in the treatment of corn seeds with H. amazonensis MC01 and H. amazonensis GL nematodes was tested. The isolate selection test for caterpillars showed that after 72 hours the nematodes H. amazonensis MC01 and S. carpocapse All were equally virulent differing from the others, reducing the caterpillar population by more than 90%. The isolate H. amazonensis GL stood out from the others, causing a mortality of 94% of pupae after 48 h. The concentration of H. amazonensis MC01 that caused the highest mortality of caterpillars in the laboratory was approximately 190 JI larve-1, and the concentration of H. amazonensis GL was 157 JI pupa-1. In greenhouse the concentrations of H. amazonensis MC01 tested did not differ among themselves. In the pupae assay the concentration that caused the highest mortality was 3500 JI vase-1. The compatibility test showed that the nematodes were compatible with NeemMax®, Fortenza 600 FS® and Cruiser 350 FS® products.